Photodegradation of norfloxacin in ice: Role of the fluorine substituent. (March 2022) - Li, Zhuojuan; Dong, Deming; Zhang, Liwen; Hua, Xiuyi; Guo, Zhiyong
Abstract: Ice is an important medium in cold regions, because it regulates the environmental behaviors and the fate of pollutants. The photodegradation of fluoroquinolone (FQ) antibiotics as emerging contaminants of concern in ice remains poorly understood. Here, the photodegradation of fluorine-containing norfloxacin (NOR) as one model of FQs in ice formed from freezing solutions was investigated. Pipemidic acid (PPA) as a structural analogue of NOR was selected to compare the effect of molecular structure on the antibiotic photodegradation in the ice. Results suggested that the photodegradation rate constant of NOR in ice relative to pure water increased by 40.0%. Both the absorbance in the absorption spectra and quantum yields of NOR in ice over water increased by 1.4 times. Direct photodegradation mainly caused the defluorination of NOR, which was more important than cleavage and oxidation of the piperazine ring by self-sensitized photooxidation in ice. The defluorination rate of NOR in the ice relative to water increased by about 12.7%. The fluorine substituent played a more important role in the NOR photodegradation in the ice, resulting in a 1.6-fold increase in the photodegradation rate constant of NOR relative to PPA. This work provides a new insight into the role of fluorine substituents in the photodegradation of fluorinated pharmaceuticals in cold regions. Graphical abstract: Image 1 Highlights: Photodegradation of typical quinolone antibiotics in ice was investigated. Norfloxacin photodegradation in ice was faster than its analogue without fluorine. Defluorination of norfloxacin in ice was greater than piperazine oxidized by ROS. Defluorination rate of norfloxacin in ice was 12.7% higher than in water. Fluorine substituent facilitated norfloxacin to segregate into liquid like regions.